A comparative life cycle analysis of wheat straw utilization modes in China. (1st March 2020) - Cheng, Guishi; Zhao, Ying; Pan, Shijiu; Wang, Xiaoqiang; Dong, Changqing
Abstract: There are abundant wheat straw resources in China. Proper treatment of wheat straw can reduce environmental pollution and environmental load while bring certain economic benefits. How to choose the right way to deal with straw is a difficult problem at present. Life cycle analysis of three wheat straw utilization modes: (1)direct combustion for electricity (2)fuel ethanol production and (3)feed production have been conducted to compare their environmental performances. Life cycle analysis results show that fuel ethanol production from wheat straw is an environment-friendly utilization mode because of its great advantages (−412mPt) in human health, ecological environment quality, climate change and natural resources. Direct combustion for electricity has certain advantages in terms of natural resources and treatment efficiency, but has greater impact (308mPt) on climate change and more emissions compared with fuel ethanol production and feed production. Feed production has great economic advantages and moderate environmental load (358mPt). It has the potential for large-scale application. The determination of the specific utilization mode should take into account the actual needs local conditions and other factors. Highlights: A comparative LCA of wheat straw utilization modes has been conducted in China. Simapro software is used to compare and analyze the utilization modes of wheat straw. Three utilization modes were use as electricity, fuel ethanol, feed. Fuel ethanol has great advantages and feed has great economic advantages. Electricity has certain advantages in terms of natural resources and efficiency.